All-atom molecular dynamics study of impact fracture of glassy polymers. II: Microscopic origins of stresses in elasticity, yielding, and strain hardening. (20th October 2020) - Tang, Zhiye; Fujimoto, Kazushi; Okazaki, Susumu
Abstract: Polycarbonate (PC) is a typical ductile polymer which first undergoes shear yielding followed by plastic deformation when subjected to stress. Although numerous theoretical models have been proposed to explain the yielding, its microscopic origin remains unclear. Therefore, we analyzed herein our previous all-atomistic molecular dynamic (MD) trajectories to investigate the microscopic origins of the yielding stress as well as the entire fracture process via rigorous stress decomposition, which considered the contributions of the system alignment and the bond, angle, and van der Waals (vdW) interactions. The affine deformation in the elastic region occurs due to bond stretching, angle bending, and separation of the vdW interacting atom pairs. Plastic deformation, which initiates upon yielding, reduces the growth rate of the bond, angle stresses and vdW stresses via the interchain collisions; meanwhile, the system alignment also contributes to an increased stress. Finally, the main chain bonds and angles are further stretched after strain softening, thereby causing strain hardening. Graphical abstract: Image 1 Highlights: Direct stress decomposition is performed using all-atomistic simulations. The amplitude of stress response is largely decided by the bond and angle stresses. The shape of yielding and strain softening is determined by van der Waals stress. Chain alignment contributes as a compensation to the intermolecular van der Waals. Plastic deformation results in a competition between bonded terms and van der Waals.